Investigation of the refractive index decrement of 3D printing materials for manufacturing breast phantoms for phase contrast imaging. (27th March 2019) - Esposito, G; Mettivier, G; Bliznakova, K; Bliznakov, Z; Bosmans, H; Bravin, A; Buliev, I; Di Lillo, F; Ivanov, D; Minutillo, M; Sarno, A; Vignero, J; et al.
Abstract: 3D breast modelling for 2D and 3D breast x-ray imaging would benefit from the availability of digital and physical phantoms that reproduce accurately the complexity of the breast anatomy. While a number of groups have produced digital phantoms with increasing level of complexity, physical phantoms reproducing that software approach have been scarcely developed. One possibility is offered by 3D printing technology. This implies the assessment of the energy dependent absorption index β of 3D printing materials for absorption based imaging, as well as the assessment of the refractive index decrement, δ, of the printing material, for phase contrast imaging studies, at the energies of interest for breast imaging. In this work we set-up a procedure and performed a series of measurements (at 30, 45 and 60 keV, at the European Synchrotron Radiation Facility) for assessing the relative value of δ with respect to that of breast tissues, for twelve 3D printing materials. The method included propagation based phase contrast 2D imaging and retrieval of the estimated phase shift map, using the Paganin's algorithm. Breast glandular, adipose and skin tissues were used as reference materials of known ratio δ / β . A percentage difference Δ δ was introduced to assess the suitability of the printing materials as tissue substitutes. The accuracy of the method (about 4%) was assessed based on the properties of PMMA and Nylon, acting as gold standard. Results show that, for the above photon energies, ABS is a good substitute for adipose tissue, Hybrid as a substitute of the glandular tissue and PET-G for simulating the skin. We plan to realize a breast phantom manufactured by fused deposition modelling (FDM) technology using ABS, Hybrid and PET-G as substitutes of the glandular and skin tissue and a second phantom by stereolithography (SLA) technology with the resins Flex, Tough and Black.